PEREGRINATION OF ARBITRATION IN INDONESIA: IS LAW NO. 30 OF 1999 A TRUE EVOLUTION OF ARBITRATION PRACTICE? - Joshua Manogar, Gregory (CV. Era Digital Nusantara, 2022)
Indonesia has recently become a favorite destination for investors and traders to do business, either investor or to trade. Indonesia as a soon to be one of business hubs in South East Asia Region has everything it needs to become not only a place to do business but also to settle business related dispute through arbitration, as Indonesia itself has ratified several important conventions such as the 1958 New York Convention and ICSID Convention, further Indonesia has already had an arbitration law which governs the whole procedure of conducting arbitration in Indonesia or enforce an award in Indonesia. This law is already more than 20 years old, which means Indonesia has gone through several economic dynamic and changes of business trends. Those changes, undeniably may affect the relevancy and effectiveness of Law No 30 of 1999 and therefore reveal the loopholes and irrelevancy of this law, such as the potential of denial of justice practice, arbitrator negligence which may result in an unenforceability of an arbitral award and unclear definition of public order, which shall be revised and repaired in the future amendment for the sake of legal certainty